THE EFFECT OF USING ANAGRAM GAME ON STUDENTS VOCABULARY ACHIEVEMENT IN TENTH GRADE - Manurung, Sartika; Lestari, Febrika Dwi; Silitonga, Harpen; Simanjuntak, Tarida Alvina (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2022)
This research investigated the effect of using the Anagram Game on students' vocabulary achievement in tenth grade at SMK Swasta Karya Jaya, addressing the identified problem of low vocabulary mastery that hinders their overall English language proficiency. Preliminary research indicated that out of 20 students, only 4 reached the minimum passing grade of 75, highlighting the need for effective vocabulary instruction strategies. The objective of this study was to determine whether the Anagram Game significantly affects students' vocabulary acquisition, specifically in nouns, verbs, and adjectives, which are foundational for English communication.Employing a quantitative research design with a pre-test and post-test control group, the study involved 40 tenth-grade students at SMK Swasta Karya Jaya, divided into an experimental group (Anagram Game) and a control group (conventional teaching). The experimental group's pre-test mean score was 72.4, and the post-test mean score was 83.45. The control group's pre-test mean score was 74.8, and the post-test mean score was 79.15. Before the independent samples t-test, data were analyzed using SPSS version 25 to ensure normality and homogeneity. The results of the data analysis indicated that the data were normally distributed and homogeneous.The independent samples t-test revealed a statistically significant difference in vocabulary achievement between the two groups (t-count = 2.108, df = 38, p < 0.05, t-table = 2.024), indicating that the Anagram Game had a positive effect on students' vocabulary acquisition. It is recommended that future research further explore different methods of the game in comparison with Anagram Game. This study provides empirical evidence supporting the use of game-based learning strategies for vocabulary instruction in senior high school settings.